Multilocus sequence analysis of Thermoanaerobacter isolates reveals recombining, but differentiated, populations from geothermal springs of the Uzon Caldera, Kamchatka, Russia - Wagner, Isaac D.; Varghese, Litty; Hemme, Christopher L.; Wiegel, Juergen (Frontiers in Microbiology, 2013)
Abstract: Thermal environments have island-like characteristics and provide a unique opportunity to study population structure and diversity patterns of microbial taxa inhabiting these sites. Strains having ≥98% 16S rRNA gene sequence similarity to the obligately anaerobic Firmicutes Thermoanaerobacter uzonensis were isolated from seven geothermal springs, separated by up to 1600 m, within the Uzon Caldera (Kamchatka, Russian Far East). The intraspecies variation and spatial patterns of diversity for this taxon were assessed by multilocus sequence analysis of 106 strains. Analysis of eight protein-coding loci (gyrB, lepA, leuS, pyrG, recA, recG, rplB, and rpoB) revealed that all loci were polymorphic and that nucleotide substitutions were mostly synonymous. There were 148 variable nucleotide sites across 8003 bp concatenates of the protein-coding loci. While pairwise FST values indicated a small but significant level of genetic differentiation between most subpopulations, there was a negligible relationship between genetic divergence and spatial separation. Strains with the same allelic profile were only isolated from the same hot spring, occasionally from consecutive years, and single locus variant sequence types were usually derived from the same spring. While recombination occurred, there was an "epidemic" population structure in which a particular T. uzonensis sequence type rose in frequency relative to the rest of the population. These results demonstrate spatial diversity patterns for an anaerobic bacterial species in a relative small geographic location and reinforce the view that terrestrial geothermal springs are excellent places to look for biogeographic diversity patterns regardless of the involved distances.